2022
DOI: 10.3389/fmicb.2022.1069254
|View full text |Cite
|
Sign up to set email alerts
|

The role of upper and lower genital tract microbiota alterations in term chorionamnionitis: A prospective study

Abstract: ObjectiveThis study aimed to compare the dynamics of lower and upper genital tract microbiota in normal term pregnancy, histological chorioamnionitis (HCA), and clinical chorioamnionitis (CCA) patients to provide a reference for the diagnosis and treatment of chorioamnionitis (CAM) patients.MethodsWe prospectively collected vaginal and cervical secretions, as well as placenta tissues, fetal membranes, and amniotic fluid from normal-term pregnant women, HCA and CCA patients. Then, we performed genomic DNA extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Li, et al ( Li et al, 2022 ) sequenced vaginal and cervical secretions from women with normal full-term pregnancy, clinical chorioamnionitis and histological chorioamnionitis, respectively, and showed that these groups had similar cervical microbiological results. Germano, et al, on the other hand, found that vaginal colonisation with Mycoplasma and Mycoplasma Ureaplasma during pregnancy was associated with poor neonatal outcome, whereas there was no significant difference in neonatal outcomes in women with Candida infection ( Germano et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Li, et al ( Li et al, 2022 ) sequenced vaginal and cervical secretions from women with normal full-term pregnancy, clinical chorioamnionitis and histological chorioamnionitis, respectively, and showed that these groups had similar cervical microbiological results. Germano, et al, on the other hand, found that vaginal colonisation with Mycoplasma and Mycoplasma Ureaplasma during pregnancy was associated with poor neonatal outcome, whereas there was no significant difference in neonatal outcomes in women with Candida infection ( Germano et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium is associated with urinary tract and surgical site infections and bacteremia, especially in a hospital-acquired setting [ 50 ]. In pregnancy, Enterococcal infection is uncommon; however, it has been identified in the amniotic fluid of women diagnosed with clinical chorioamnionitis [ 51 ]. Ncib et al demonstrated that the presence of vaginal-derived Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota in the upper vaginal tract of term healthy pregnancies, histological chorioamnionitis (HCA), and clinical chorioamnionitis (CCA) patients were examined using 16S rRNA sequencing. Microorganisms in the intrauterine environment significantly decreased in the CCA group (48). Chorioamnionitis has a significant association with preterm premature rupture of fetal membrane (PPROM), preterm delivery, and FIRS resulting in increased morbidity and mortality of neonatal (49,50).…”
Section: The Causes and Outcome Of Chorioamnionitismentioning
confidence: 99%